2018
DOI: 10.2478/sgem-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Assessment of a Single Pile Subjected to Lateral Load

Abstract: A three-dimensional finite element technique was used to analyse single pile lateral response subjected to pure lateral load. The main objective of this study is to assess the influence of the pile slenderness ratio on the lateral behaviour of single pile. The lateral single pile response in this assessment considered both lateral pile displacement and lateral soil resistance. As a result, modified p-y curves for lateral single pile response were improved when taking into account the influence lateral load mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The Mohr-Coulomb model can describe the elastoplastic characteristics of soil to some extent, and is widely applied in lateral load pile models [42]. The simulation of the soil in this paper adopts the elastoplastic Mohr-Coulomb model, which can effectively assess the effect of landslide surges.…”
Section: Soil Modelmentioning
confidence: 99%
“…The Mohr-Coulomb model can describe the elastoplastic characteristics of soil to some extent, and is widely applied in lateral load pile models [42]. The simulation of the soil in this paper adopts the elastoplastic Mohr-Coulomb model, which can effectively assess the effect of landslide surges.…”
Section: Soil Modelmentioning
confidence: 99%
“…The case study of the soil-pile system of four-multi story building were formulated with Plaxis. The boundary condition for the finite element method for piles into soil media (40x40x30) m according to [16], the dimensions of the soil body surface of a cube shape (10D) from the center of the pile diameter, and (5D) below the pile base as illustrated in Figure 1. This study's model consists of two parts: material soil simulate with elastic perfectly plastic with three square layers (Mohr-Coulomb model).…”
Section: Formulation Problem Of Study In Plaxis-3d 2020 Programmentioning
confidence: 99%
“…Abbas et al [7] In their study, they modeled a 3dimensional single pile with the finite element method and examined the effect of the geometric shape of the pile and the L/D ratio on the lateral load carrying capacity of the pile. Accordingly, they concluded that the load carrying capacity of square piles is better than round piles, and the pile head rotation values are lower at a certain L/D ratio.…”
Section: Introducti̇onmentioning
confidence: 99%